Electronic Data Processing and Teacher Placement. - Dilts, Harold E. (Journal of Teacher Education)
The article focuses on the application of electronic data processing in teacher placement practices at Iowa State University in Ames, Iowa. The author suggests that the criteria for establishing electronic data processing includes the idea that such process would retain personal services and contacts provided for teacher candidates and employing officials and that there are advantages in machine processing over the addition of facilities and clerical staff. The coding of the data used in the electronic processes includes those designating geographic area and community size and those using teaching fields. Significantly, the processes can applied to office procedures such as the registering of teacher candidates, school districts, and data processing centers.